2006
DOI: 10.1001/archpedi.160.12.1255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Life Skills Intervention for Increasing Physical Activity in Adolescent Girls

Abstract: A life skills-oriented physical education curriculum may need to be combined with other approaches to increase the magnitude of effects on physical activity behavior in predominantly African American high school-aged girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 38 publications
2
95
1
Order By: Relevance
“…23 The trial was designed to test the effects of a life skills-oriented physical activity intervention, conducted in PE class, on physical activity and cardiorespiratory fitness relative to the standard PE class in high school girls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 The trial was designed to test the effects of a life skills-oriented physical activity intervention, conducted in PE class, on physical activity and cardiorespiratory fitness relative to the standard PE class in high school girls.…”
Section: Methodsmentioning
confidence: 99%
“…23,27 This instrument was interviewer administered in which each participant was asked to recall her sleep and physical activity for the previous 7 days. The questionnaire is divided into 3 periods of the day: morning, afternoon, and evening.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While other whole school models have used social cognitive theory [34,35], the trans-theoretical model [26], a social-ecological approach [36][37][38], or no theory [39], the HPSS intervention was informed by the Self Determination Theory (SDT) [40,41]. This theory posits that building autonomy, competence, and relatedness will enhance personal motivation to engage in a health behavior, thus these constructs are reflected in the four CORE components of the HPSS intervention presented below.…”
Section: Hpss Developmentmentioning
confidence: 99%
“…Such findings have inspired further research into associating physical activity with lifestyle activities, such as at school and recreational play. A study of more than 200 ninth grade (age 14-15 years) girls in Baltimore [15] revealed that integrating life skills instruction into physical education at school improved cardiovascular fitness and reduced overall time spent in sedentary behaviors. Outside school, access to neighborhood parks and recreation facilities may offer healthier alternatives to the often sedentary activities of the home environment.…”
Section: Integrating Activity Into Daily Lifementioning
confidence: 99%